Frailty and nutritional status in Egyptian diabetic seniors at Ain Shams Geriatrics Hospital; a cross-sectional study - Elham Arif; Manar Mohamed Ellaban; Maram Magdy Shaat (The Egyptian Journal of Internal Medicine)
Abstract Background Frailty is a prevalent geriatric syndrome in Egypt and worldwide; it is characterized by multisystem dysregulation that increases the susceptibility to detrimental health consequences. Patients with malnutritionare more susceptible to developing frailty, especially diabetic seniors. Hence, this cross-sectional study aims to measure the prevalence of frailty and malnutrition among diabetic seniors' Egyptian patients and to determine the relationship between them. Methods A cross-sectional study of 116 diabetic seniors, sixty years of age and above, was conducted in Ain Shams University Geriatric Hospital from April 2024 to October 2024. Study participants received a comprehensive geriatric assessment including socio-demographic data, detailed medical history, Charlson comorbidity index (CCI), and glycated hemoglobin. Nutritional assessment using body mass index (BMI) and mini nutritional assessment long form. Assessment of Frailty using Fried Frailty Phenotype. Results Prevalence of Frailty and malnutrition was 68.1% and 44.8% respectively. Univariate significant associations existed between Frailty and malnutrition, as well as between frailty and polypharmacy, the Charlson comorbidity index, comorbidities number, Diabetes duration and complications, and BMI. While binary logistic regression concluded that prolonged diabetes duration and increased comorbidities number were the only predictors of Frailty. Conclusions Our results concluded that Frailty and malnutrition are prevalent among diabetic Egyptian seniors. Malnutrition is significantly associated with Frailty in diabetic patients with prolonged duration and higher comorbidities number. Hence, nutritional screening is of utmost importance for diabetic seniors and its prevention may reduce risk of frailty.